2015
DOI: 10.1088/0268-1242/30/12/125005
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characterization of DC and small-signal parameters of 150 nm and 250 nm gate-length AlGaN/GaN HEMTs grown on a SiC substrate

Abstract: This paper investigated the temperature effects on the performance of the AlGaN/GaN high electron mobility transistor (HEMT) with a 150 nm and 250 nm gate length on a SiC substrate over a temperature range of −40 to 150°C including experimental characterization, modelling and analysis by on-wafer measurements up to 50 GHz. All the DC and small signal parameter variations with ambient temperature on the same set of devices have been reported for the first time. The temperature coefficient of all the DC and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
5
17
0
Order By: Relevance
“…However, a small increase in drain resistance (R d ) was also observed at higher V D . Similar behaviour of extrinsic parameters with temperature has been reported in the published work [18]. The extracted C g (C gs + C gd ) at different V D was shown in Figure 8(a).…”
Section: Resultssupporting
confidence: 86%
“…However, a small increase in drain resistance (R d ) was also observed at higher V D . Similar behaviour of extrinsic parameters with temperature has been reported in the published work [18]. The extracted C g (C gs + C gd ) at different V D was shown in Figure 8(a).…”
Section: Resultssupporting
confidence: 86%
“…With a two-port network, the small signal model of the AlGaN/GaN HEMT device can be depicted as in Figure 3 [17,18]. Utilizing the y-parameter analysis, the drain-source current (I DS ) and the transconductance (G m ) of the device can be derived as:…”
Section: Two-port Network Analysismentioning
confidence: 99%
“…From Table 10, it has been observed that proposed method is more general as instead of an assumed linear function, it uses curve fitting method involving polynomials. Except for Reference 20, none of the referred works in discussion have quantified the deviation in predicted and measured values of the extrinsic and intrinsic parameters. Even in comparison to the method reported in Reference 20, error % is better indicating comparability with the method.…”
Section: Comparative Studymentioning
confidence: 99%
“…Except for Reference 20, none of the referred works in discussion have quantified the deviation in predicted and measured values of the extrinsic and intrinsic parameters. Even in comparison to the method reported in Reference 20, error % is better indicating comparability with the method. Hence, the proposed method is more general and hence can be applied to devices across technology.…”
Section: Comparative Studymentioning
confidence: 99%
See 1 more Smart Citation